Resilience Capacity and Food Security: Is There a Relationship Between Household Resilience Profiles and Food Security Outcomes? - Bekhzod Egamberdiev (ZBW – Leibniz Information Centre for Economics, 2024)
Resilience thinking has gained prominence in research and policy debates in food security analysis. This article aims to estimate the effect of household resilience capacity on food security outcomes. The manuscript uses the Cambodia Living Standard Measurement – Plus Survey 2019-2020. The measurement of resilience capacity is done through Resilience Index Measurement and Analysis – II by FAO. In the RIMA approach, the manuscript also applies Latent Profile Analysis (LPA) to cluster households, categorizing homogenous resilience levels through “Low Resilient,” “Medium Resilient,” and “High Resilient” profiles. In the estimation strategy, the current study proposes a step-by-step analytical approach for using the propensity score matching (PSM) techniques with LPA to draw causal effects of resilience profiles on dietary diversity and food expenditure per capita. The findings generally confirm that “Medium Resilient” and “High Resilient” households have positive effects on food security outcomes compared to those labelled as “Low Resilient” households.
Keywords: Q18; Q13; O20; C01; 330; Resilience capacity; food security; latent profile analysis; average treatment effect; propensity score matching